THE EFFECT OF THE REMAINING BUDGET CALCULATIONS AND BUDGET REFOCUSING ON EXPENDITURE FOR COVID-19 HANDLING - Nova, Indana; Andayani, Tutut Dwi; Hidayah, Rini (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study investigates the effect of the Remaining Budget Calculation and Budget Refocusing on Expenditure for Handling Covid-19 in districts/cities governments in Central Java in 2020-2021. This study took the population of district/city governments in Central Java. This study used a purposive sampling method in order to obtain 20 districs/cities that were feasible to study. This study uses multiple linear regression analysis techniques. The results obtained show that Remaining Budget Calculations and Budget Refocusing have a simultaneous effect on Expenditure for Handling Covid-19. Partially, the Budget Refocusing variable has an effect on Expenditure for Handling Covid-19, while the Remaining Budget Calculation has no effect on Spending for Handling Covid-19 in Regency/City Governments in Central Java in 2020-2021. The coefficient of determination in this study is 46.8%, which means that the ability of all independent variables in the form of Remaining Budget Calculations and Budget Refocusing in explaining the dependent variable in the form of Covid-19 Handling Expenditures is 46.8% and the remainder is influenced by variables outside the regression model.